Dynamics of microflora condition in patients with acute bacterial prostatitis exposed to combination therapy - V. V. Masljakov; O. N. Pavlova; E. A. Pronina; F. P. Sultonov; A. E. Burekeshev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The study included 30 patients who were diagnosed with acute bacterial prostatitis. The average age of the patients was 32 ± 2 years. The study included patients who gave their consent to participate, who did not have concomitant pathology, which was documented, whose age ranged from 18 to 40 years. Patients over 40 years of age with chronic diseases, patients with an established diagnosis of chronic prostatitis were excluded. All patients were divided into two groups of 15 people. The first (group 2) included patients with OBP who were treated with antibacterial drugs in combination with photodynamic therapy and magnetolaser exposure. The second group (group 1) included 15 patients who received antibacterial therapy and magnetolaser exposure without photodynamic therapy. As a result of the study, it was found that the use of combination therapy leads to faster (on the third day) changes in the microflora and relief of symptoms of acute bacterial prostatitis.